High-Strength Ultra-Fine-Grained Hypereutectic Al-Si-Fe-X (X = Cr, Mn) Alloys Prepared by Short-Term Mechanical Alloying and Spark Plasma Sintering - Průša, Filip; Bláhová, Markéta; Vojtěch, Dalibor; Kučera, Vojtěch; Bernatiková, Adriana; Kubatík, Tomáš František; Michalcová, Alena (Materials (Basel, Switzerland), 2016)
In this work, Al-20Si-10Fe-6Cr and Al-20Si-10Fe-6Mn (wt %) alloys were prepared by a combination of short-term mechanical alloying and spark plasma sintering. The microstructure was composed of homogeneously dispersed intermetallic particles forming composite-like structures. X-ray diffraction analysis and TEM + EDS analysis determined that the α-Al along with α-Al15(Fe,Cr)₃Si₂ or α-Al15(Fe,Mn)₃Si₂ phases were present, with dimensions below 130 nm. The highest hardness of 380 ± 7 HV5 was observed for the Al-20Si-10Fe-6Mn alloy, exceeding the hardness of the reference as-cast Al-12Si-1Cu-1 Mg-1Ni alloy (121 ± 2 HV5) by nearly a factor of three. Both of the prepared alloys showed exceptional thermal stability with the hardness remaining almost the same even after 100 h of annealing at 400 °C. Additionally, the compressive strengths of the Al-20Si-10Fe-6Cr and Al-20Si-10Fe-6Mn alloys reached 869 MPa and 887 MPa, respectively, and had virtually the same values of 870 MPa and 865 MPa, respectively, even after 100 h of annealing. More importantly, the alloys showed an increase in ductility at 400 °C, reaching several tens of percent. Thus, both of the investigated alloys showed better mechanical properties, including superior hardness, compressive strength and thermal stability, as compared to the reference Al-10Si-1Cu-1Mg-1Ni alloy, which softened remarkably, reducing its hardness by almost 50% to 63 ± 8 HV5.
Keywords: mechanical properties; microstructure; mechanical alloying; spark plasma sintering